Transnational collective bargaining in Europe. A proposal for a European regulation on transnational collective bargaining - Even, Jozef Harmen (Den Haag, 2008)
"This dissertation provides recommendations for realising European legislation on the conclusion of transnational collective labour agreements. It is of interest for anyone involved in (European) collective labour law, private international law, comparative law and the European social dialogue. Prior to discussing how to shape such European legislation, it is argued that transnational collective bargaining seems increasingly worth while to pursue, but that a new legal framework is necessary. These conclusions are drawn after scrutinising the challenges for and the role of the European social partners over the last decades are scrutinised, discussing the Europeanisation of collective bargaining, critically reviewing the European social dialogue and inventorying and weighing the advantages and disadvantages of transnational collective bargaining. It is subsequently argued that a new legal framework on transnational collective bargaining should be based on national collective law traditions. Therefore, the national laws of the Member States of the EU are compared, with a focus on the Netherlands, Germany, Belgium and the UK. The European protection of the freedom of association, the right to collective bargaining and the right to strike is analysed separately. The research results in a suggestion for a European regulation on transnational collective bargaining, which includes important topics such as the proper legal basis for European legislation, bargaining agents, bargaining levels, representativity, the binding power of transnational collective labour agreements, applicable law and enforcement."